PENGELOLAAN ARSIP ELEKTRONIK TERHADAP EFISIENSI KERJA KARYAWAN BAGIAN STAF KANTOR PADA PT ABC DI BATAM - Shinta Wahyu Hati; Sri Nurhayani (Inovbiz: Jurnal Inovasi Bisnis, 2016)
Abstract: The management of E-archive is very affecting the efficiency of employ- yee’s performance. The importance of the electronic archival management system will increase the efficiency of employee’s work rate. This research method uses a quantitative approach to the type of explanatory research. The research object is the staff office employees at PT ABC is a company engaged in the electronics bu- siness in Batam manufkatur. The sample in this research were 65 respondents, by using the method of data collection questionnaires. Methods of analysis of this study using multiple linear regression. The findings showed that the variables move documents electronically, storing documents electronically, and index docu- ments positive influence on employee efficiency while controlling access to the va- riable does not affect the work efficiency of employees. Research findings showed that the overall electronic records management variables significantly influence the efficiency of work of employees. Keywords:  Archival  Management,  E-Archive,  and  The  Efficiency  of  Em-ployee’s Performance